PERANCANGAN SISTEM INFORMASI AKUNTANSI LAPORAN KEUANGAN (STUDI KASUS PADA PT. 212 SIAGA PROPERTY MANAGEMENT) - Ony Widilestariningtyas; Dwi Rahayu Boedikartini; Rio Yunanto (Labkat Press KA FTIK UNIKOM, 2012)
212 Siaga Property Management make a move area of service of security. When the writer research at financial administration, they making of financial statement still use the Microsoft Office Excel as a means of calculate. For the problems hence writer take the title